Methinx you could use rudimentary algebraic methods to arrive at your goal, consider:
@array1=qw(A B C); @array2=qw(1 2 3);
is equivalent to/can be re-written as:
@array1=('A', 'B', 'C'); @array2=('1', '2', '3');
Also, the requirement can be re-written as:
%hash = ( array1=>[('A','B','C')], array2=>[('1','2','3')] };
So, substituting for ('A','B','C') & ('1','2','3'), into the re-written required result, gives:
%hash = ( array1=>[@array1], array2=>[@array2] };
But, [@array] can be/usually is written as \@array, hence,
%hash = ( array1=>\@array1, array2=>\@array2 };
As required - also discoverable by reference to perlreftut - as moritz has previously suggested.

A user level that continues to overstate my experience :-))

In reply to Re: Two arrays into hash by Bloodnok
in thread Two arrays into hash by Anonymous Monk

Use:  <p> text here (a paragraph) </p>
and:  <code> code here </code>
to format your post; it's "PerlMonks-approved HTML":